Effect of substitution rate of soya bean cake by faba beans (Vicia faba) on meat quality of black of Thibar and fat tail Barbary breed lambs - Damergi C.; Boukhris H. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
This study aims to compare the effect that different level of faba bean distributed to two local Tunisian lamb breeds on the quality of meat during 5 days postmortem. Thirty male black of Thibar and fat tail Barbary lamb breeds were divided into three groups. After weaning the lambs were offered access to one of three different iso-nitrogen and iso-energetic concentrates, where soya beans were substituted at 0%, 10% or 20% by faba beans cake in diets. At the end of the trial (75 days), all lambs were slaughtered. Colour (L,a*,b*), pH and shear force of longissimus dorsi and semitendinous muscle were significantly affect by breed and nitrogen source (p<0.001). This study showed that, lambs receiving faba bean had tender meat and better quality scores than meat from lambs receiving only soya bean.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)